Eye-tracking the semiotic effects of layout on viewing print advertisements. - Damaskinidis, George; Kourdis, Evangelos; Zantides, Evrpides; Sykioti, Eleni (Public Journal of Semiotics, 2017)
The print advertisement produces meaning for its readers through the interaction of a complex system of semiotic elements. Understanding this meaning is based on readers' ability to follow the established reading conventions of their culture. The article describes a study that uses eye-tracking technology to examine readers' interaction with the semiotic elements of two print advertisements. The relation between print advertisements and semiotics is informed by intersemiotic analysis and the reading path concept. The advertisements' layout is rearranged to form two sets of texts: one original advertisement and a modified version. We have calculated the time sequence in which visual and verbal areas attract attention, the amount of time spent on them and the depth of attention paid to the areas read. The results show how layout re-arrangement affects reading behaviour, such as reading the smallest visual first and the target text sequentially without visual elements interrupting the reading, or having the same point of entry in both the original and the modified advertisements.